(5x - 1)(3x-2)
First = 15x
Outer = -10x
Inner = -3x
Last = 2
Answer = 15x - 10x - 3x +2
Simplified = 2x + 2
2006-12-07 12:12:10
·
answer #1
·
answered by Love_Forever 3
·
1⤊
1⤋
Story:
I'm 53, have two engineering degrees and am currently in the graduate math program. I never heard of foil until I taught remedial algebra as a GTA.
I recommend setting up the multiplication like you would a regular multiplication problem and just multiply:
5x-1
3x-2
--------
15x^2-3x-10x+2
then collect your x terms:
15x^2 -13x+2
Why fool around with that foil nonsense. This works for any size polynomial. Actually, it works for any two bracketed expressions.
Down with foil!
2006-12-07 12:14:56
·
answer #2
·
answered by modulo_function 7
·
0⤊
0⤋
Foil is First outer inner last First you take 5x*3x then you take 5x*-2 then -1*3x then -1*-2 which gives you 15x^2-13x+2
2006-12-07 12:14:05
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
15x^2 - 13x + 2
by ^2 i mean x squared. don't know how to make it show a superscripted 2
2006-12-07 12:13:05
·
answer #4
·
answered by Dale B 3
·
0⤊
0⤋
15x^2-13x+2
2006-12-07 12:15:59
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
15x^2-13x+2
2006-12-07 12:12:53
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
(5x - 1)(3x - 2)
F:: 15x^2
O: -10x
I: -3x
L: 2
(5x - 1)(3x - 2) = 15x^2 - 13x + 2
QED
2006-12-07 12:47:04
·
answer #7
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
First = 15x2
Outer = -10x
Inner = -3x
Last = 2
Answer = 15xx - 13x + 2
I don't know how to type x square.
2006-12-07 12:13:56
·
answer #8
·
answered by som5enak 2
·
0⤊
0⤋